Penggunaan Total Station Dan Autocad Civil 3D Untuk Perencanaan Grading - Adi, Wahyu Tamtomo; Aghastya, Adya (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2017)
This study was structured with the aim of carrying out topographic measurements and analyzing grading planning in the API Madiun campus area. The study was conducted using a Total Station measurement tool and a 3D Autocad Civil 3D imaging tool. Surveyor personnel used in carrying out measurements are surveyors who are trained using Total Station equipment. The study produced ten benchmark point (BM) locations as a measurement reference in areas within the Madiun API land. The topographic analysis results from the contour map identified the Madiun API land area as relatively flat with the difference between the lowest and highest elevation of 5.132 m with an average slope of 3.32%. The grading plan shows that there are two main areas that require landfills with the total pile volume requirement of 8,281.4 m3. Evaluation of the implementation of measurements shows the need for supervision and evaluation so as not to make mistakes that can occur by the measurement implementer. The use of Autocad Civil 3D software tools facilitates and accelerates the process of depicting engineering and land grading planning. Measurement with Total Station and depiction with Autocad Civil 3D needs to be optimized by integration into the lecture syllabus in order to become one of the soft skill competencies possessed by graduates of Building Engineering and Railways of API Madiun.